1997
DOI: 10.1039/a703773b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and thermal behaviour of Fe0.65Co0.35-MgAl2O4 and Fe0.65Ni0.35-MgAl2O4 nanocomposite powders

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
4
20
1
Order By: Relevance
“…Other catalysts (Co, Ni, and Fe/Co/Ni binary alloys) have been studied using the appropriate MgAl 2 O 4 -based solid solutions, with cobalt and equimolar Fe/Co alloys giving the best results. [12][13][14][15] Mg 1-x Co x O powders were also studied as precursors and are notably interesting because a simple soaking in HCl allows one to separate the CNTs from the CNT-Co-MgO powders formed upon reduction in H 2 /CH 4 . 2,3 The so-obtained CNTs, 90% of which are SWNTs and double-walled CNTs (DWNTs) with a diameter between 0.7 and 3 nm, are dispersed individually rather than in bundles and have a very high specific surface area (ca.…”
Section: Introductionmentioning
confidence: 99%
“…Other catalysts (Co, Ni, and Fe/Co/Ni binary alloys) have been studied using the appropriate MgAl 2 O 4 -based solid solutions, with cobalt and equimolar Fe/Co alloys giving the best results. [12][13][14][15] Mg 1-x Co x O powders were also studied as precursors and are notably interesting because a simple soaking in HCl allows one to separate the CNTs from the CNT-Co-MgO powders formed upon reduction in H 2 /CH 4 . 2,3 The so-obtained CNTs, 90% of which are SWNTs and double-walled CNTs (DWNTs) with a diameter between 0.7 and 3 nm, are dispersed individually rather than in bundles and have a very high specific surface area (ca.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, much smaller (<5 nm) surface particles, in rather large quantities, are formed at higher temperature (1000 • C, maybe also at lower temperatures, notably 900 and 950 • C but with too small a size to be detected by FEG-SEM) and seem to correspond to the metallic Fe produced by each zirconia crystallite located at the surface. They could be attributed to ␥-Fe [24,25] solid solutions have revealed that the reduction of the more easily reducible transition metal cation promotes the reduction of the less reducible one(s), resulting in the formation of Fe/Cr, Co/Fe/Ni and Co/Fe alloy nanoparticles, respectively. However, this promoting effect is not thought to be probable if the two M/M x O y systems are too far apart in the Ellingham diagram that plots the variation of the free energy G of the oxidation reaction versus temperature, as is the case for Fe/Fe 2 O 3 and Zr/ZrO 2 , where ZrO 2 is considered to be unreducible.…”
Section: Resultsmentioning
confidence: 98%
“…In earlier works, we have shown that oxide solid solutions prepared by decomposition and calcination of oxalate mixtures or by nitrate/urea combustion are also potentially high-performance precursors because the as-such produced materials feature a very homogeneous distribution of the desired metallic ions in their structures. Using the appropriate temperature and duration in the reduction process of these precursors, one is able to precisely control the micro/nanostructure of Fe/Cr-Al 2 O 3 [15][16][17][18][19], Fe/CrCr 2 O 3 [20], Fe/Co/Ni-MgO [21,22] and Fe/Co/Ni-MgAl 2 O 4 [23][24][25] nanocomposite powders. Although Ni-Y 2 O 3 -ZrO 2 composites are claimed to be materials of greater importance for solid-oxide fuel cells [26], Fe-ZrO 2 ceramic-matrix micro-or nanocomposites have been seldom studied.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of results obtained on these materials are given in recent publications. [1][2][3][4][5][6][7][8][9][10][11][12] To create nano-micro or nano-nano ceramic-based composites with excellent performance, a process for achieving a homogeneous dispersion of secondary particles in the matrix is required. The present study focused on developing a route using porous alumina preforms to obtain Ni-Al 2 O 3 nanocomposite powders with a uniform distribution of nano-sized metal particles in the ceramic matrix.…”
Section: Introductionmentioning
confidence: 99%